2008
DOI: 10.2202/1556-3758.1360
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Microwave Treatment Technique for Bacterial Decontamination of Raw Meat

Abstract: The present study developed and verified a 'cold' microwave (MW) treatment that could lead to the inactivation of two common pathogenic species of bacteria, Escherichia coli and Staphylococcus aureus, in raw meats. A number of experimental conditions were designed and tested to maximise MW exposure without overheating the samples. The non-thermal effect was maximised by multiple exposure to attain efficient MW threshold intensities. It was shown that at sub-lethal temperatures repeated exposure using high freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…A cavity characterization option was also available that allowed evaluation of the performance of a material in the cavity to assist in determining the optimum processing conditions as described in our previous design. 25 …”
Section: Microwave Apparatusmentioning
confidence: 99%
See 4 more Smart Citations
“…A cavity characterization option was also available that allowed evaluation of the performance of a material in the cavity to assist in determining the optimum processing conditions as described in our previous design. 25 …”
Section: Microwave Apparatusmentioning
confidence: 99%
“…Previous studies indicated that during microwave sterilization of bacteria performed at 508C, around 30% reduction in bacterial numbers was achieved as a result of the heating effect alone and not radiation. 25 Therefore, for the threshold treatment temperature, 458C was preferred, as it is the temperature at which the target pathogens were determined to be unaffected by heat. The experiments were prepared using the highest available frequency (lowest wavelength) of 18 GHz.…”
Section: Treatment Of Inoculated Sample With Microwave Radiationmentioning
confidence: 99%
See 3 more Smart Citations